Особливості програмного регулювання у контексті дослідження феномена міжнародних програм - Бабін, Б.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье исследована категория программы с использованием методологии программного менеджмента и правовые наук с целью определения природы феномена международные программ. Сделан вывод о значении международные программ как нормативного акта специфической природы. The category of program is studied, at the article with using the methodology of the program management and law sciences with a target of distinguishing of the phenomenon of the international programs. The summary on the importance of the international programs as a normative act with a specific nature was done.